Hereditary twenty-nail dystrophy in a Sicilian family. Issue 5 (October 1982) - Pavone, L; Volti, S Li; Guarneri, B; Rosa, M La; Sorge, G; Incorpora, G; Mollica, F
Abstract : Over three successive generations four members of a Sicilian family showed early onset, slowly progressive dystrophy of the finger and toe nails, without any other anomalies or skin signs. Histological examination performed in two patients enabled us to discount lichen planus and other underlying diseases. The hereditary and idiopathic nature of the disease is underlined and a classification of the dystrophies affecting all the 20 nails is proposed.